2019
DOI: 10.1038/s41598-019-42476-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of two (short-term) storage methods on load to failure testing of murine bone tissue

Abstract: Since mechanical testing of bone quality is often delayed following euthanasia, the method of bone storage is of high importance in animal studies. Different storage methods may cause a change in the properties of bone tissue during mechanical testing. Therefore, the aim of this study was to investigate the biomechanical effects of two different fixation methods for bone tissue. We hypothesized that there is a difference between the load to failure values between the two groups. The tibias of fifteen 18-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…These different storage methods each present with advantages and disadvantages. In a recent paper, our group could demonstrate that short-term storage of murine tibial bone tissue do not affect the load to failure, independent of the used method 10 . The lack of short-term detrimental effects as evidenced in our murine study 10 is supported by the findings of Beaupied et al 18 who showed that one month storage in alcohol or deep-freezing seemed to induce no harmful effect on densitometric, microarchitectural and biomechanical parameters of rat femurs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These different storage methods each present with advantages and disadvantages. In a recent paper, our group could demonstrate that short-term storage of murine tibial bone tissue do not affect the load to failure, independent of the used method 10 . The lack of short-term detrimental effects as evidenced in our murine study 10 is supported by the findings of Beaupied et al 18 who showed that one month storage in alcohol or deep-freezing seemed to induce no harmful effect on densitometric, microarchitectural and biomechanical parameters of rat femurs.…”
Section: Discussionmentioning
confidence: 94%
“…For the purpose of long-term bone storage, several methods have been described in the literature. We have recently 10 reported that cryopreservation may be more suitable for long-term storage than other methods, such as using paraformaldehyde or formalin. Ethanol for example leads to an extensive damage to the triple-helical structure of collagen depending on temperature and storage time 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Different storage methods may cause a change in the properties of bone tissue during mechanical testing. A study demonstrated that paraformaldehyde solution does not influence the biomechanical properties of bone even over a two-week period ( Tiefenboeck et al., 2019 ). Furthermore, no differences in mechanical properties were observed up to 12 and 24 months of cryopreservation at -80 °C ( Matter et al., 2001 ; Tiefenboeck et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%